2021
DOI: 10.3390/ijms23010154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Differentially Expressed Genes under Salt Stress in Olive

Abstract: Climate change, currently taking place worldwide and also in the Mediterranean area, is leading to a reduction in water availability and to groundwater salinization. Olive represents one of the most efficient tree crops to face these scenarios, thanks to its natural ability to tolerate moderate salinity and drought. In the present work, four olive cultivars (Koroneiki, Picual, Royal de Cazorla and Fadak86) were exposed to high salt stress conditions (200 mM of NaCl) in greenhouse, in order to evaluate their to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 82 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…The expression of the stress‐related genes ( OePOD , OeP5CS , OeRD19A and OeNHX7 ) was investigated in the infested olive trees treated with MT, GB and ALA using quantitative real‐time PCR as reported by Mousavi et al . (2022) with slight modifications. In brief, total RNA was isolated from leaves, and cDNA was synthesized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the stress‐related genes ( OePOD , OeP5CS , OeRD19A and OeNHX7 ) was investigated in the infested olive trees treated with MT, GB and ALA using quantitative real‐time PCR as reported by Mousavi et al . (2022) with slight modifications. In brief, total RNA was isolated from leaves, and cDNA was synthesized.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses were carried out using Qiagen QuantiTect SYBR Green PCR kit. Gene-specific primers previously designed were used in the amplification process (Dastkar et al, 2020;Mousavi et al 2022). ACTIN gene was utilized as an internal reference control (Dastkar et al, 2020).…”
Section: Measurement Of the Vegetative Growth And Physio-biochemical ...mentioning
confidence: 99%
“…Cold stress is a major issue for olive trees, as it can have significant impacts on tree growth, flowering, productivity, and olive oil quality. Olive trees are well adapted to warm Mediterranean climates ( Melgar et al., 2009 ; Ponti et al., 2014 ; Mousavi et al., 2019 ; Mousavi et al., 2022 ) but are susceptible to low temperatures, especially to out-of-season ones and can be damaged irreversibly. Previous studies have shown that low temperatures can result in a range of morphological, physiological, and biochemical changes in olive trees, including changes in the concentration of plant hormones, photosynthesis, and antioxidant defense systems ( Gómez-del-Campo and Barranco, 2005 ; Arias et al., 2015 and Lodolini et al., 2016 ; Arias et al., 2017 ; Mougiou et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants initiate genome-wide transcriptional regulation to cope with salt stress. Genes related to osmotic adjustment, ion transport, and antioxidant are up- or down-regulated by salt stress ( Gupta & Huang, 2014 ; Mousavi et al, 2021 ). For example, plants deploy some low-molecular-weight osmolytes such as proline, to mitigate the adverse effects of salt stress on cell osmoticum ( Mansour & Ali, 2017 ; Yang & Guo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%